Complement System Part II: Role in Immunity - Merle, Nicolas S.; Noe, Remi; Halbwachs-Mecarelli, Lise; Fremeaux-Bacchi, Veronique; Roumenina, Lubka T. (Frontiers in Immunology, 2015)
The complement system has been considered for a long time as a simple lytic system, aimed to kill bacteria infecting the host organism. Nowadays this vision has changed and it is well accepted that complement is a complex innate immune surveillance system, playing a key role in host homeostasis, inflammation and in the defense against pathogens. This review discusses recent advances in the understanding of the role of complement in physiology and pathology. It starts with a description of complement contribution to the normal physiology (homeostasis) of a healthy organism, including the silent clearance of apoptotic cells and maintenance of cell survival. In pathology, complement can be a friend or a foe. It acts as a friend in the defense against pathogens, by inducing a direct killing by C5b-9 membrane attack complex by triggering inflammatory responses with the anaphylatoxins C3a and C5a and helps the mounting of an adaptive immune response, involving antigen presenting cells, T- and B- lymphocytes. But it can be also an enemy, when pathogens hijack complement regulators to protect themselves from the immune system. Also examples will be discussed, where inadequate complement activation becomes a disease cause, including atypical hemolytic uremic syndrome (aHUS), C3 glomerulopathies (C3G) and systemic lupus erythematosus (SLE). Age related macular degeneration (AMD) and cancer will be described as examples showing that complement contributes to a large variety of diseases, far exceeding the classical examples of diseases associated with complement deficiencies. Finally, we discuss complement as a therapeutic target.